Visit-to-visit SBP variability and risk of atrial fibrillation in middle-aged and older populations. Issue 12 (10th December 2022) - Wang, Chi; Sun, Yizhen; Xin, Qian; Han, Xu; Cai, Zefeng; Zhao, Maoxiang; Yun, Cuijuan; Zhang, Sijin; Hou, Ziwei; Chen, Shuohua; Wu, Shouling; Xue, Hao
Abstract : Objective: We sought to examine the relationship between visit-to-visit variability of SBP and incident atrial fibrillation in middle-aged and older population. Methods: This prospective cohort study included 26 999 participants aged 50 years or older at study entry. Visit-to-visit variability of SBP was defined as the average real variability (ARV) of three values of SBP from the examinations of 2006, 2008, and 2010. We categorized participants into four groups according to the quartiles of ARV. Incident atrial fibrillation cases were identified via ECG during biennial resurveys, and reviewing medical insurance record and discharge registers. We used Cox regression models to evaluate the hazard ratios and 95% confidence intervals (CI) for incident atrial fibrillation. Results: After an average follow-up of 9.24 years, a total of 420 atrial fibrillation cases were identified. The incidence of atrial fibrillation from the lowest to the highest quartiles of SBP variability were 1.23, 1.53, 1.81 and 2.19 per 1000 person-years, respectively. After adjusting for potential confounders, including mean blood pressure, we found a graded association between SBP variability and risk of atrial fibrillation. Participants in the third quartile and the highest quartile were associated with 35 and 53% higher risk of developing atrial fibrillation, respectively, compared with participants in the lowest quartile [hazard ratio (95% CI), 1.35 (1.01–1.82) and 1.53 (1.15–2.04)]. The results persisted across sensitivity analyses. Conclusion: Increased visit-to-visit variability of SBP is a strong predictor of incident atrial fibrillation in middle-aged and older population. Evaluation of long-term SBP variability could help to identify individuals at higher risk of atrial fibrillation.